Balancing the risks to individual and society: a systematic review and synthesis of qualitative research on antibiotic prescribing behaviour in hospitals. Issue 4 (April 2019) - Krockow, E.M.; Colman, A.M.; Chattoe-Brown, E.; Jenkins, D.R.; Perera, N.; Mehtar, S.; Tarrant, C.
Summary: Background: Antimicrobial resistance is a global health threat, partly driven by inappropriate antibiotic prescriptions for acute medical patients in hospitals. Aim: To provide a systematic review of qualitative research on antibiotic prescribing decisions in hospitals worldwide, including broad-spectrum antibiotic use. Methods: A systematic search of qualitative research on antibiotic prescribing for adult hospital patients published between 2007 and 2017 was conducted. Drawing on the Health Belief Model, a framework synthesis was conducted to assess threat perceptions associated with antimicrobial resistance, and perceived benefits and barriers associated with antibiotic stewardship. Findings: The risk of antimicrobial resistance was generally perceived to be serious, but the abstract and long-term nature of its consequences led physicians to doubt personal susceptibility. While prescribers believed in the benefits of optimizing prescribing, the direct link between over-prescribing and antimicrobial resistance was questioned, and prescribers' behaviour change was frequently considered futile when fighting the complex problem of antimicrobial resistance. The salience of individual patient risks was a key barrier to more conservative prescribing. Physicians perceived broad-spectrum antibiotics to be effective and low risk; prescribing broad-spectrum antibiotics involved low cognitive demand and enabled physicians to manage patient expectations. Antibiotic prescribing decisions in low-income countries were shaped by a context of heightened uncertainty and risk due to poor microbiology and infection control services. Conclusions: When tackling antimicrobial resistance, the tensions between immediate individual risks and long-term collective risks need to be taken into account. Efforts to reduce diagnostic uncertainty and to change risk perceptions will be critical in shifting practice.